2022
DOI: 10.3390/cancers14133252
|View full text |Cite
|
Sign up to set email alerts
|

A RAS-Independent Biomarker Panel to Reliably Predict Response to MEK Inhibition in Colorectal Cancer

Abstract: Background: In colorectal cancer (CRC), mutations of genes associated with the TGF-β/BMP signaling pathway, particularly affecting SMAD4, are known to correlate with decreased overall survival and it is assumed that this signaling axis plays a key role in chemoresistance. Methods: Using CRISPR technology on syngeneic patient-derived organoids (PDOs), we investigated the role of a loss-of-function of SMAD4 in sensitivity to MEK-inhibitors. CRISPR-engineered SMAD4R361H PDOs were subjected to drug screening, RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…In 2021, Boos SL et al further demonstrated that metastatic CRC PDOs introduced by KRASG12D are an ideal platform to model chemotherapy tolerance ex vivo and AURKA was found to be a therapeutic target in liver metastatic CRC ( Boos et al, 2022 ). Besides, the SMAD4 ( Pfohl et al, 2022 ) mutation and FGFR1 and OXTR ( Tung et al, 2021 ) mutations were knocked out using CRIPSR/CAS9 technology in colon cancer PDOs for reversing drug resistance. Using an organoid platform based on CRISPR/Cas9 knockout technology, Seino T et al found that GATA6 expression regulated Wnt niche independence, which was mainly acquired non-genetically through mutations of driver genes (KRASG12V, CDKN2A, TP53, and SMAD4) during pancreas tumorigenesis ( Seino et al, 2018 ).…”
Section: Application Of Organoids In Gi Tumorsmentioning
confidence: 99%
“…In 2021, Boos SL et al further demonstrated that metastatic CRC PDOs introduced by KRASG12D are an ideal platform to model chemotherapy tolerance ex vivo and AURKA was found to be a therapeutic target in liver metastatic CRC ( Boos et al, 2022 ). Besides, the SMAD4 ( Pfohl et al, 2022 ) mutation and FGFR1 and OXTR ( Tung et al, 2021 ) mutations were knocked out using CRIPSR/CAS9 technology in colon cancer PDOs for reversing drug resistance. Using an organoid platform based on CRISPR/Cas9 knockout technology, Seino T et al found that GATA6 expression regulated Wnt niche independence, which was mainly acquired non-genetically through mutations of driver genes (KRASG12V, CDKN2A, TP53, and SMAD4) during pancreas tumorigenesis ( Seino et al, 2018 ).…”
Section: Application Of Organoids In Gi Tumorsmentioning
confidence: 99%
“…CRC is the third most diagnosed cancer in the world, and the main cause of death is metastases (1). CRC can be classified into different subtypes, which are characterized by specific molecular and morphological alterations (2).…”
Section: Introductionmentioning
confidence: 99%